Chewable Versus Regular Carbamazepine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
A comparison of chewable and regular carbamazepine (CBZ tablets) in 44 children receiving chronic CBZ monotherapy is reported from the IWK Children's Hospital, Halifax, Nova Scotia.